2019
DOI: 10.1039/c9ta01876j
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes for advanced lithium ion batteries using silicon-based anodes

Abstract: Recent progress in electrolytes from the liquid to the solid state for Si-based anodes is comprehensively summarized in this review article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 107 publications
1
82
0
Order By: Relevance
“…Hence, an efficient approach to stabilize this SEI layer is the use of additives, which most of the times are designed to be consumed during the initial formation the SEI layer, but can serve also to improve the electrochemical stability window of the electrolyte, or to enhance the safety (flame retardants) . Common additives include vinyl carbonate (VC), fluoroethylene carbonate (FEC) or lithium bis(oxalate)borate (LiBOB) .…”
Section: Challenges and Limitation In Si And Ge Anodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, an efficient approach to stabilize this SEI layer is the use of additives, which most of the times are designed to be consumed during the initial formation the SEI layer, but can serve also to improve the electrochemical stability window of the electrolyte, or to enhance the safety (flame retardants) . Common additives include vinyl carbonate (VC), fluoroethylene carbonate (FEC) or lithium bis(oxalate)borate (LiBOB) .…”
Section: Challenges and Limitation In Si And Ge Anodesmentioning
confidence: 99%
“…VC decomposes into polycarbonates at about 1 V versus Li/Li + , the presence of double bonds in its structure rend it is more susceptible to reduction . FEC decomposes at 1.3 V versus Li/Li + into a passivating layer that is much more compact resulting in a lower mass transfer resistance and improved capacity retention . FEC decomposes into polyenes and a high concentration of Li 2 O which prevents the diffusion of HF through the SEI .…”
Section: Challenges and Limitation In Si And Ge Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The major components of the SEI layer is lithium salt (e.g., ROCO 2 Li, Li 2 CO 3 , and LiF) and polycarbonate (Chen et al, 2007). Electrolyte additive can leave their chemical signatures in the SEI layer which make it the most effective strategy to manipulate the targeted SEI property (Xu et al, 2019). Martin's group (Zeng et al, 2018) adopted FEC and VC as additives for nano Si electrode, and it was found that they can form a robust and thermal stable SEI that was rich in polycarbonates species which contribute to an enhanced thermal stability of the lithiated silicon electrode, thus increase the exothermic temperature by about 50 • C. Many other typical SEI-modifier additives, such as phosphorus (Mai et al, 2015;Song et al, 2016), nitrogen (Abu-Lebdeh and Davidson, 2009;Chen et al, 2016b), boron (Lee et al, 2014b;Kim et al, 2017), sulfur (Zuo et al, 2014), or silicon containing species (Chen et al, 2017b;Wang et al, 2017a), are widely studied in thermal stability enhancement of both SEI and CEI, some dual-functionalgroup additives, such as N,N-diallyic-diethyoxyl phosphamide (DADEPA) (Cao et al, 2013), tris(trimethylsilyl)phosphate (TMSP) (Rong et al, 2014), tris(trimethylsilyl)borate (TMSB) (Liu et al, 2013) are also intensively studied.…”
Section: Construction a Thermal Stable Seimentioning
confidence: 99%
“…The pulverization of silicon particles makes the Coulombic efficiency low in the first circle, and it is difficult to maintain good cycle stability . A uniform carbon coating prevents direct contact between the silicon particles and the electrolyte, promoting stable solid electrolyte layer formation . It has the most stable solid‐electrolyte interface (SEI) formed at the cracks .…”
Section: Silicon‐based Composite Materialsmentioning
confidence: 99%